2020
DOI: 10.1097/qco.0000000000000664
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus: a reemerging infection

Abstract: Purpose of review Scrub typhus, caused by Orientia tsutsugamushi, is a widely neglected disease which is gaining global momentum because of its resurgence patterns. The disease is now being reported in newer regions as well as areas previously endemic areas. In this review, we aim to comprehensively review the data available to assist physicians in making an accurate diagnosis and appropriate management of the disease. Recent findings Several diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…[ 2 12 ] In a review done by John R and Varghese GM, the incidence of AKI among patients with scrub typhus admitted to a tertiary care teaching hospital in south India was found to be 18%. [ 13 ] The incidence of AKI in our study is close to these studies. Electrolyte abnormalities in the form of hyponatremia and hypokalemia are seen in some patients with AKI.…”
Section: Discussionsupporting
confidence: 87%
“…[ 2 12 ] In a review done by John R and Varghese GM, the incidence of AKI among patients with scrub typhus admitted to a tertiary care teaching hospital in south India was found to be 18%. [ 13 ] The incidence of AKI in our study is close to these studies. Electrolyte abnormalities in the form of hyponatremia and hypokalemia are seen in some patients with AKI.…”
Section: Discussionsupporting
confidence: 87%
“…The case fatality rate in those with ARDS was 18% [ 6 ]. In a recent review on scrub typhus, John and Varghese reported that pneumonia progressing to ARDS was seen in more than one-third of patients requiring hospitalization and was one of the common complications [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scrub typhus, a potentially life-threatening disease with an enormous incidence in the Asia–Pacific Rim, remains remarkably neglected [ 12 ]. Outdoor work is the high-risk occupation associated with scrub typhus [ 13 ].…”
Section: Discussionmentioning
confidence: 99%